2003
DOI: 10.2337/diabetes.52.9.2321
|View full text |Cite
|
Sign up to set email alerts
|

The Hepatic Vagus Mediates Fat-Induced Inhibition of Diabetic Hyperphagia

Abstract: Diabetic rats both overeat high-carbohydrate diet and have altered hypothalamic neuropeptide Y (NPY) and corticotropin-releasing factor (CRF). In contrast, a high-fat diet reduces caloric intake of diabetics to normal, reflected by normal hypothalamic NPY and CRF content. How the brain senses these changes in diet is unknown. To date, no hormonal changes explain these diet-induced changes in caloric intake. We tested whether the common branch of the hepatic vagus mediates the fat signal. We presented fat in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 51 publications
2
53
0
Order By: Relevance
“…Furthermore, streptozotocin-induced hyperphagia was reportedly reversed by hepatic expression of protein phosphatase-1 (29), suggesting that altering hepatic metabolism modulates appetite. Vagal pathways from the liver to the brain mediate the fat-induced changes in hypothalamic neuropeptides and feeding behavior in diabetic rats (30). Taken together with these observations, through appetite modulation, the liver also holds promise as a target for treatment of diabetes with obesity.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, streptozotocin-induced hyperphagia was reportedly reversed by hepatic expression of protein phosphatase-1 (29), suggesting that altering hepatic metabolism modulates appetite. Vagal pathways from the liver to the brain mediate the fat-induced changes in hypothalamic neuropeptides and feeding behavior in diabetic rats (30). Taken together with these observations, through appetite modulation, the liver also holds promise as a target for treatment of diabetes with obesity.…”
Section: Discussionmentioning
confidence: 79%
“…27 Furthermore, we showed that in diabetic rats, the hepatic vagus mediates diet-induced changes in expression of POMC and NPY mRNA. 12,13 These findings suggest that, at least in diabetic rats, the afferent neural input from the liver/intestine contributes to the response of the melanocortin and NPY system to a fat diet. Indeed, the alterations in POMC mRNA levels owing to HF or HFHS choice diets are prevented by hepatic vagotomy; however, alterations in NPY mRNA levels when fed HF or HFHS choice diets were not.…”
Section: Discussionmentioning
confidence: 91%
“…through the hepatic vagal (HV) nerve). 12,13 As we observed differential responses in hypothalamic neuropeptide expression to the diets, we examined hormonal responses and investigated the involvement of neuronal feedback signals in these diet-induced hypothalamic responses.…”
Section: Introductionmentioning
confidence: 99%
“…However, LCR rats did demonstrate a greater increase in EI during the acute HFD, evoking a greater 3-day weight gain, increased adiposity, and a twofold higher EB in the LCR vs. HCR. Previous findings show that increased EI on a HFD is due to a predisposition to store dietary calories in adipose and decreased whole body (6) and liver-specific FAO (7), resulting in liver-derived afferent signals to increase food intake (21). Therefore, we posit that the phenotype of the low aerobic capacity rat (increased trafficking of fatty acids to adipose and reduced whole body and hepatic fatty acid oxidation) may drive subsequent elevated acute EI in a feed-forward process that increases EB and worsens steatosis outcomes.…”
Section: Discussionmentioning
confidence: 99%